The French National Animal Health Surveillance Platform: an innovative, cross-sector collaboration to improve surveillance system efficiency in France and a tangible example of the One Health approach - Dupuy, Céline; Locquet, Célia; Brard, Christophe; Dommergues, Laure; Faure, Eva; Gache, Kristel; Lancelot, Renaud; Mailles, Alexandra; Marchand, Justine; Payne, Ariane; Touratier, Anne; Valognes, Aurèle; et al. (Frontiers in Veterinary Science, 2024)
The French National Animal Health Surveillance Platform (NAHSP) was created in 2011. This network of animal health stakeholders was set up to improve surveillance efficiency for all health risks that threaten animal health, as well as zoonoses affecting human health. The NAHSP steering committee decides on the strategies and program of activities. It is composed of eleven institutions from both the public and private sectors (policy-makers, scientific institutions, and representatives of farmers, veterinarians, hunters, and laboratories). A coordination team guarantees the program’s implementation and coordinates the activities of the different working groups (WGs). Each WG is composed of technical experts with scientific, legal and field knowledge from the sectors of animal health (livestock, companion animals, and wildlife), human health, and environmental health. Some WGs focus on a specific disease or health indicator, such as African swine fever or cattle mortality, while others cover cross-cutting topics, such as epidemic intelligence, or are dedicated to supporting epidemiological investigations, such as the Q fever WG. The NAHSP is innovative because it is based on the concepts of consensus among participants, collaboration, and interdisciplinarity. Each proposal designed to improve surveillance is jointly developed by all the stakeholders involved, thus ensuring its sustainability and acceptability among stakeholders. This process also has added value for decision makers. As a pioneer platform, the NAHSP inspired the creation of two additional national surveillance platforms in 2018, one for plant health and the other for food chain safety. Both are organized in the same way as the NAHSP, which created a framework to place the emphasis on a One Health approach. Four WGs, for instance, are common to the three national surveillance platforms. This article aims to present this innovative approach to improve surveillance efficiency that could be of interest to other European countries or that could be rolled out at the European level.